Visual results after primary intraocular lens implantation or contact lens correction for aphakia in the first year of age - Autrata, Rudolf; Rehurek, Jaroslav; Vodicková, Kristina (Ophthalmologica. Journal international d'ophtalmologie. International journal of ophthalmology. Zeitschrift fur Augenheilkunde, 2005)
PURPOSE: The optimal role of intraocular lenses (IOLs) in infants remains a controversial topic. Some ophthalmologists advocate correction with a contact lens (CL), whereas others recommend an IOL correction. Our study compared visual acuity, ocular alignment, retreatment rate and binocular vision outcomes in children treated with these two methods at our clinic. METHODS: This study included 41 children with unilateral congenital cataract who underwent cataract surgery with posterior capsulorhexis and anterior vitrectomy, coupled with (IOL group, n=18) or without (CL group, n=23) primary IOL implantation. All infants underwent the first surgery during the first 12 months of their life and they were operated on in the period from 1994 to 1999. The mean age at surgery was 3.11+/-2.65 months (range: 28 days to 11 months). All patients were prescribed the same half-time reduced occlusion therapy. Good cooperation of the parents and good compliance with patching were the necessary conditions to include a patient in the study. Between January and February 2003, the final visual acuity and binocular vision outcomes were examined. RESULTS: The mean final visual acuity (logarithm of the minimum angle of resolution) of the operated eye was 0.43+/-0.33 for the IOL group and 0.58+/-0.39 for the CL group (p=0.14). The mean interocular difference in visual acuity was 0.22+/-0.29 for the IOL group and 0.56+/-0.31 for the CL group (p=0.042). The reoperation rate was 78% in the IOL group compared with 35% in the CL group (p=0.017). Esotropia or exotropia of more than 8 prism diopters were present in 55% of children (10/18) in the IOL group compared with 83% of children (19/23) in the CL group (p=0.039). CONCLUSIONS: We suggest that correction of aphakia after unilateral congenital cataract surgery with primary IOL implantation results in improved visual acuity, improved binocular vision outcome and less occurrence of strabismus, but a higher rate of complications requiring reoperation. Further studies with a larger pediatric patient group are necessary to confirm the optimal treatment of aphakia after unilateral congenital cataract extraction.
Keywords: kontaktní čočky; Infant; Contact Lenses; novorozenec; Refraction, Ocular; výsledek terapie; refrakce oka; katarakta; lidé; Infant, Newborn; pooperační komplikace; afakie po kataraktě; Treatment Outcome; následné studie; Cataract; Vision, Binocular; Incidence; retrospektivní studie; Follow-Up Studies; Postoperative Complications; incidence; kojenec; Aphakia, Postcataract; Strabismus; pseudofakie; Pseudophakia; Lens Implantation, Intraocular; vidění binokulární; implantace nitrooční čočky; zraková ostrost; Visual Acuity; Retrospective Studies; strabismus; Humans